2011
DOI: 10.1111/j.1365-2966.2011.18759.x
|View full text |Cite
|
Sign up to set email alerts
|

Age patterns in a sample of spiral galaxies

Abstract: We present the burst ages for young stellar populations in a sample of six nearby (<10 Mpc) spiral galaxies using a differential pixel‐based analysis of the ionized gas emission. We explore this as an alternative approach for connecting large‐scale dynamical mechanisms with star formation processes in disc galaxies, based on burst ages derived from the Hα to far‐UV (FUV) flux ratio. Images of each galaxy in Hα were taken with Taurus Tunable Filter and matched to FUV imaging from GALEX. The resulting flux ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 120 publications
(188 reference statements)
4
24
0
Order By: Relevance
“…Previous works have tried to relate the spiral arms with the star formation (see e.g. Ivanov 1985;Allen et al 1986;Tilanus & Allen 1993;Stedman & Knapen 2001;Knapen et al 2010;Sánchez-Gil et al 2011). These studies have shown the relation between the star formation and the spiral structure using different gas components over different parts of a large set of galaxies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works have tried to relate the spiral arms with the star formation (see e.g. Ivanov 1985;Allen et al 1986;Tilanus & Allen 1993;Stedman & Knapen 2001;Knapen et al 2010;Sánchez-Gil et al 2011). These studies have shown the relation between the star formation and the spiral structure using different gas components over different parts of a large set of galaxies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Early proposals for triggering involved shock compression of incoming clouds (Woodward 1976), diffuse cloud formation in a phase transition driven by thermal instabilities (Shu et al 1973), diffuse cloud formation in the magnetic instability of Parker (1966;Mouschovias et al 1974), cloud-cloud collisions (Vogel et al 1988;Koda & Sofue 2006), and giant cloud formation by gravitational instabilities in the shocked gas (Elmegreen 1979;. Color and age gradients downstream from the shock suggest star formation triggering (Sheth et al 2002;Tamburro et al 2008;Martínez-García et al 2009;Egusa et al 2009;Martínez-García & González-Lópezlira 2011;Sánchez-Gil et al 2011), but differential compression of old stars and gas (Elmegreen 1987) and between H i and CO gas phases (Louie 20 European Space Agency Research Fellow. et al 2013) can produce structures that mimic age gradients.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the UV flux traces less massive stars with timescales of a few hundred Myr (Kennicutt 1998;Iglesias-Paramo et al 2004). The Hα luminosity declines more rapidly than the UV continuum luminosity, which leads to a decrease in the Hα to UV SFR ratio with increasing starburst age (Sánchez-Gil et al 2011). Thus, the Hα to UV SFR ratio carries important information about the SFH and the duration of the SF episode of a galaxy.…”
Section: Star Formation Historiesmentioning
confidence: 99%